Incidence of type 2 diabetes in Mexico. Results of The Mexico City Diabetes Study after 18 years of follow-up. - Clicerio González-Villalpando; Claudio Alberto Dávila-Cervantes; Mireya Zamora-Macorra; Belem Trejo-Valdivia; María Elena González-Villalpando (Instituto Nacional de Salud Pública, 2014)
Objective. To estimate the incidence of type 2 diabetes (T2D) in Mexican population. Materials and methods. Population based prospective study. At baseline (1990), the population at risk (1939 non-diabetic adults 35-64 years) was evaluated with oral glucose tolerance test. Subsequent similar evaluations were done (1994, 1998, 2008). American Diabetes Association diagnostic criteria were applied. Results. The period of observation was 27842 person-years, the cumulative incidence of T2D was 14.4 and 13.7 per 1000 person-years for men and women, respectively. Incidence was 15.8, 15.7 and 12.7 per 1 000 person-years for the second (1994), third (1998) and fourth (2008) follow-up phases, respectively. The mean age at diagnosis was 44 years for prevalent cases and 56 years for incident cases. Conclusions. This is the first estimate of long-term incidence of T2D in Mexican population. The incidence is among the highest reported worldwide. It remained with few changes throughout the study period.